Parasite Soup: Faith and Science in the History of Parasitology - Blaschke, Jeremy D. (Zygon, 2022)
Popular conceptions of the relationship between science and religion often emphasize the mutual compatibility but segregation of these two authoritative domains. However, along the uncertain border between these two spheres exist many questions that appear to influence and be influenced by both scientific and theological evidence. For biologists, the gruesome details of parasite biology and behavior illuminate a shadow in nature where science and theology must intersect—did a loving creator God design parasites? Here, I explore the writings and experiments of the early fathers of parasitology who established and matured a new scientific discipline while deeply integrating their theological beliefs with their scientific investigations. I argue that modern scientists can, and often should, follow in the footsteps of our scientific forefathers and intentionally allow our theological presuppositions to inspire scientific experiments, especially in these important boundary-crossing subjects. In doing so, I believe we may advance scientific understanding of the way reality is by asking unexpected questions and uncover deeper truths about the character of God as revealed in his intricately complex and eternally fascinating creation.